2019
DOI: 10.3389/fmicb.2018.03259
|View full text |Cite
|
Sign up to set email alerts
|

Picoeukaryotic Diversity And Activity in the Northwestern Pacific Ocean Based on rDNA and rRNA High-Throughput Sequencing

Abstract: Picoeukaryotes play an important role in the biogenic element cycle and energy flow in oligotrophic ecosystems. However, their biodiversity and activity are poorly studied in open ocean systems, such as the northwestern Pacific Ocean, which is characterized by a complex hydrological setting. Here, we investigated the diversity and activity of picoeukaryotes in the northwestern Pacific Ocean using high-throughput sequencing targeting the V9 region of 18S rDNA and rRNA. Our results showed that the DNA picoeukary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 74 publications
(104 reference statements)
1
12
2
Order By: Relevance
“…Moreover, Wang et al (2019) found abundant MALV-II in the subtropical northwestern Pacific Ocean in the spring. However, overrepresentation of the 18S rDNA sequence numbers of MALV-II than their rRNA counterparts was also observed.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Moreover, Wang et al (2019) found abundant MALV-II in the subtropical northwestern Pacific Ocean in the spring. However, overrepresentation of the 18S rDNA sequence numbers of MALV-II than their rRNA counterparts was also observed.…”
Section: Discussionmentioning
confidence: 93%
“…The appearance of MALV‐II implied that host–parasite interactions might often occur in this region in winter. Moreover, Wang et al () found abundant MALV‐II in the subtropical northwestern Pacific Ocean in the spring. However, overrepresentation of the 18S rDNA sequence numbers of MALV‐II than their rRNA counterparts was also observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S3 ) and after removal of metazoan OTUs and OTUs < 1% total reads, the final OTU count was 201 with variable distributions per population per sample (Table 2 ). Compared to protist communities collected and size-fractionated by filtration, reportedly composed of > 1,000 OTUs 38 42 , the low OTU richness is a reminder that our cell sorting protocol allowed the focused targeting of small pigmented eukaryote populations. The low OTU counts (3–42) for each population (Table 2 ) further reflect the accuracy of the sorting method and the near taxonomic purity of some of the sorted populations.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to DNA, RNA is unstable in extracellular conditions, microbial community structures inferred from rRNA sequencing (hereafter RNA sequencing) can exclude sequences from dissolved extracellular pool, dormant cells and dead materials (Not et al, 2009). Thus, the RNA-based approach was used to identify the active species or groups in environmental samples (Massana et al, 2015;Hu et al, 2016;Wang et al, 2019). The RNA: DNA ratio (calculated by relative sequence abundance) has been used as an index for the relative metabolic activity in protist (Hu et al, 2016;Wu and Liu, 2018).…”
Section: Introductionmentioning
confidence: 99%